Development of Speaking Skills in ELT through a Textbook - Krčálová, Eliška (Univerzita Pardubice, 2018)
This bachelor thesis is concerned with developing speaking skills in ELT through a textbook. The theoretical part deals with a definition of a textbook as a teaching aid and its roles and functions within the educational processes. The following chapters define the concept of second language speaking competence, speaking skills as a means for development of communicative competence and classification of speaking activities. The practical part of the thesis is based on the content analysis of speaking activities from the chosen textbook. The main aim of the research is to discover the opportunities for the development of speaking skills in ELT and therefore, the second language speaking competence.
Rozvoj řečové dovednosti mluvení v anglickém jazyce pomocí učebnice
Keywords: učebnice; řečová dovednost mluvení; mluvní kompetence; mluvní aktivity; textbooks; speaking skills; second language speaking competence; speaking activities